Performance evaluations of fast frequency-hopped spread-spectrum communication systems with partial-band noise jamming and multitone jamming - Teh, Kah Chan. (2010)
This thesis contains the formulations on theoretical performance analyses of var-ious fast frequency-hopped (FFH)binary frequency-shift-keying (BFSK)spread-spectrum (SS)systems with different jamming and channel environments. Two types of commonly encountered jamming waveforms, namely, the partial-band noise jamming (PBNJ)and the multitone jamming (MTJ), are studied in de-tail. Both non-fading and fading channels are considered. The effects of additive white Gaussian noise (AWGN)are also taken into consideration. The bit-error rate (BER)expressions presented in this thesis are applicable to higher diver-sity levels without much extra computational complexity. This important feature allows us to study the system performance at higher diversity levels.